DEVELOPMENT OF MATHEMATICS MODULE WITH THE CONTEXTUAL APPROACH TO THE DISCUSSION RULES, PERMUTATION, AND COMBINATION THROUGH THINK PAIR SHARE STRATEGY - Yopanika Naurosa Khusnayani; Julan Hernadi (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Limitation of learning resources is one factor that makes students difficult to understand a subject matter. One of the teaching materials that can help students' learning activities is modules. This study aims to develop the mathematics module that uses the contextual approach in sub-material the counting rules, permutations and combinations through think pair share strategies and to determine the appropriateness of the modules developed. The development procedure is adopted from the research and development that developed by Borg and Gall in Sugiyono (2014) including the step of identifying the potential and problems, collecting information, product designing, validation of product design, revising the product design, the pilot phase of products and product revision. Mathematics module developed based on the principals of contextual approach on Muslich, Mansur (2008). These products have been through the steps of revision based on advice and suggestions of media and subject matter experts as well as students' response to the module. The results showed from validations criteria and students' responses to the module. Based on an assessment by subject matter experts obtained an average score of 84 which satisfies good criteria, media experts obtained an average score of 93 which satisfies good criteria and results of students' response to the module also satisfy good criteria with an average score that is 110,21. These results mean the mathematics module is appropriate to use in the learning of mathematics.